2016
DOI: 10.1161/circulationaha.115.019474
|View full text |Cite
|
Sign up to set email alerts
|

Regional Systems of Care Demonstration Project

Abstract: Background Up to 50% of patients fail to meet ST-segment elevation myocardial infarction (STEMI) guideline goals recommending a first-medical-contact (FMC)-to-device time of <90 minutes for patients directly presenting to percutaneous coronary intervention (PCI)-capable hospitals and <120 minutes for transferred patients. We sought to increase the proportion of patients treated within guideline goals by organizing coordinated regional reperfusion plans. Methods We established leadership teams, coordinated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(29 citation statements)
references
References 29 publications
(24 reference statements)
1
28
0
Order By: Relevance
“…The project involved 484 hospitals (171 PCI‐capable hospitals) and 1253 EMS agencies in 16 regions using standard data collection and regional treatment protocols from 2012 to 2014 7, 8. We found that quality of care improved for EMS‐transported patients with STEMI with and without OHCA.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The project involved 484 hospitals (171 PCI‐capable hospitals) and 1253 EMS agencies in 16 regions using standard data collection and regional treatment protocols from 2012 to 2014 7, 8. We found that quality of care improved for EMS‐transported patients with STEMI with and without OHCA.…”
Section: Discussionmentioning
confidence: 98%
“…This study uses data from the Mission: Lifeline STEMI Accelerator project that was organized and executed between July 1, 2012 (2012Q3), and March 31, 2014 (2014Q1), in 16 US regions 7, 8. The intervention was initiated on the basis that, although the number of PCI‐capable hospitals in recent years has increased by almost 50% and 90% of Americans currently live within 60 minutes of a PCI‐capable facility, the organization of the healthcare system, including a highly fragmented EMS system, hinders coordination between EMS providers and hospitals 8.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations